Catalase Protects Biofilm of Staphylococcus aureus against Daptomycin Activity - Cristina El Haj; Mads Lichtenberg; Karen Leth Nielsen; Thomas Bjarnsholt; Peter Østrup Jensen (MDPI AG, 2021)
Daptomycin is recommended for the treatment of Staphylococcus aureus infections due to its bactericidal activity. However, its mechanism of action is poorly understood. The involvement of reactive oxygen species (ROS) in the bactericidal activity of daptomycin has been proved against planktonic S. aureus, but not against the biofilm of S. aureus. Therefore, we evaluated if ROS contributes to the effect of daptomycin against biofilm of S. aureus. Biofilms of wild type, catalase deficient and daptomycin-resistant S. aureus strains were grown in microtiter-plates. After three days, the biofilms were exposed to daptomycin with or without thiourea in the presence of a ROS indicator. After overnight incubation, the amount of ROS and the percentage of surviving bacteria were determined. The bacterial survival was higher and the amount of ROS was lower in the wild type than in the catalase deficient biofilm, demonstrating a protective effect of catalase against daptomycin. The induction of cytotoxic ROS formation by daptomycin was verified by the addition of thiourea, which reduced the amount of ROS and protected the wild type biofilm against high concentrations of daptomycin. Accordingly, only the highest concentration of daptomycin reduced the bacterial survival and increased the ROS formation in the resistant biofilm. In conclusion, daptomycin induced the production of cytotoxic levels of endogenous ROS in S. aureus biofilm and the presence of catalase protected the biofilm against the lethality of the induced ROS.